The Effect of the Solar Radiation Intensity and the Wave Length on the Efficiency of the Silicon Solar Cell (Latakia University Journal -Basic Sciences Series, 2020)
This study has included the effect of the solar radiation intensities, which are in the field  practically and theoretically on the voltage, the current and the silicon solar cell efficiency. The purpose of this study is having the optimal use of the solar modules in order to produce the electric power required to provide energy to the loaded needed. This study showed that the minimum practical value of the efficiency was at a solar radiation of , and the maximum value was  at a solar radiation of  at . In addition, the minimum theoretical value of the efficiency was at a solar radiation of , and the maximum value was  at the radiation of at the same temperature . We also found the maximum practical value of the efficiency at a wave length of  and it was , and the maximum theoretical value of the efficiency was at a wave length of and was at and a solar radiation intensity of